PENGARUH STRUKTUR MODAL, HARGA SAHAM DAN INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PADA SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI - Permatasari, Anita; Flora Mita Ndruru (Ekomania, 2024)
This study aims to analyze the influence of capital structure, stock price, and intellectual capital on the financial performance of manufacturing companies operating in the consumer goods sector listed on the Indonesia Stock Exchange. The research employs a quantitative method, collecting secondary data from 30 manufacturing companies operating in the consumer goods industry sector during the period of 2020-2022. Multiple linear regression analysis is used to test the relationship between the dependent variable, financial performance, and the independent variables, namely capital structure, stock price, and intellectual capital. The research results show that capital structure, share prices and intellectual capital have a significant influence on financial performance. The results of this research state that capital structure has an effect on financial performance in the consumption sector for the 2020-2022 period. The second result is that share prices have no effect on the financial performance of manufacturing companies in the consumption sector for the 2020-2022 period. The third result is that intellectual capital has no effect on the financial performance of manufacturing companies in the consumption sector for the period 2020-2022